Learning orientation and export performance in Nigeria: the moderating effect of export knowledge - Abubakar, Mukhtar Salisu; Abdul Rahim, Norhuda; Raja Yusof, Raja Nerina; Yahya, Mohamed Hisham (Gadjah Mada University, 2025)
This study explores the influence of learning orientation as an antecedent of SME export performance among Nigerian SMEs through the moderating role of export knowledge. This article opted for descriptive research using a survey design to collect data from owners or managers of exporting SMEs in Nigeria. Two hundred seventy-eight (278) respondents participated in this study using a convenient sampling technique; partial least square structural equation modeling (PLS-SEM) was utilized for data estimation. The results established that learning orientation positively affects SMEs’ export performance. In addition, export knowledge significantly moderates the relationship between learning orientation and export performance. The article contributes by broadening the body of knowledge and providing invaluable information for understanding SMEs’ export performance determinants in developing economies like Nigeria, as recommended by scholars. It also contributes to the recent streams of empirical investigation that seek to enhance the comprehension of the resources needed for successful export operations.